Chipped Stone Industries of Attica, Southern Greece: the assemblages of a Bronze Age (Early Helladic II) site at Phaleron Bay - Kakavakis, Odysseas (Journal of Greek Archaeology, 2023)
Though less known than the archaeology of the historic periods, Attica has a rich prehistoric past. Over the last decades, the number of prehistoric sites has increased significantly (Figure 1). The chipped stone industries are predominantly composed of obsidian, a homogeneous volcanic glass of dark grey to black color, opaque or semi-translucent, that fractures conchoidally and, thus, is perfectly suitable for producing flaked tools. The nearest sources of high-quality obsidian are found on Melos Island in the Cyclades, located c. 150km from the shores of Attica in a straight line.